Caminhos para uma agricultura e pecuária sustentáveis: intenções, práticas agroecológicas e desafios climáticos - Werneck, Rhayane Pires (2025)
Agricultural intensification and the growing demand for food have led to significant environmental challenges, including biodiversity loss, pest proliferation, and climate-driven pressures on production systems. This thesis explores different but interconnected pathways toward more sustainable agriculture and livestock systems by integrating behavioral, ecological, and climatic perspectives. In the first chapter, we investigate the psychological and social factors influencing dairy farmers’ intentions to adopt Best Management Practices (BMPs) in Goiás, Brazil, using the Theory of Planned Behavior. The findings highlight the importance of attitudes and perceived behavioral control, while revealing unexpected resistance linked to social norms. The second chapter presents a systematic review on the use of companion plants for pest suppression in agricultural systems, synthesizing empirical evidence and identifying knowledge gaps regarding traditional practices in Brazil. The results confirm the effectiveness of plant-based strategies, especially intercropping and trap cropping, and advocate for the integration of local ecological knowledge into scientific research. The third chapter models future distributions of three major crop pests (Spodoptera frugiperda, Helicoverpa armigera, and Diatraea saccharalis) under climate change scenarios (SSP2-4.5 and SSP5-8.5), revealing species-specific responses and potential shifts in pest pressure across the Americas. Collectively, the chapters highlight the need for context-aware strategies that combine technical innovation, farmer engagement, and anticipatory planning to ensure sustainable agricultural transitions in a changing world.